If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -23 = 36 Reorder the terms: -23 + -6x = 36 Solving -23 + -6x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + -6x = 36 + 23 Combine like terms: -23 + 23 = 0 0 + -6x = 36 + 23 -6x = 36 + 23 Combine like terms: 36 + 23 = 59 -6x = 59 Divide each side by '-6'. x = -9.833333333 Simplifying x = -9.833333333
| -4+(-8)-16-(9)= | | -5x-12=15 | | Y=-13+4(x+2) | | 4-x=-2x-7 | | 2(2y-7)+2y=106 | | x=2(20)-7 | | Y=30-2(x+3) | | -8+(-6)+20= | | Y=14-2(x-5) | | 3x+6=-222 | | 2x+2y=106 | | mx^2-(2m-1)x+m+1=0 | | 2v-6+8=14 | | 5x-2=23x | | b+4=-4b+4 | | 2y^2+3y(2y)=10 | | 1x+2=1x+7 | | 6x+20=1x+3 | | 6*3+3=3(3)+12 | | 10x+17=2x+15 | | 5x.8=0 | | 1x+10=5x+10 | | -5x-11=44 | | t^2=2+2t | | x=-3+3y | | 10y^2-10=0 | | t^2-2t-2=0 | | x+6y=-3 | | y=-2(5)+13 | | y=3/5x+2 | | -11*-11= | | 0=5x-25 |